Effect of stacking blocks on the low field magnetic refrigeration in nanocrystalline Pr2Co7 compound. (September 2018) - Fersi, R.; Bouzidi, W.; Mliki, N.; Bessais, L.
Abstract: In the present work, we report on magnetocaloric properties of nanocrystalline Pr2 Co7 compounds in its two polymorphic forms. Magnetic measurements show a second order magnetic transition around T C of 580 K and 600 K for, respectively for hexagonal (2:7H) and rhombohedral (2:7 R) structures. At a magnetic field change of 1.6 T, the magnetic entropy change −△S max M = 3.7 J/kg.K for 2:7 R structure, which is much more higher than 2:7H one (−ΔS max M = 1.1 J/kg.K). Furthermore, these results show that the magnetocaloric effect is sensitive to the stack configuration. The temperature dependence of the magnetization (M vs. T) and the Arott plots around the second order magnetic transition for this compound are reported. The relative cooling power (RCP) is around 103 J/kg and 8.5 J/kg for 2:7 R and 2:7H structure, respectively. Based on these results, we conclude that Pr2 Co7 compound with rhombohedral structure (2:7 R) has potential to be magnetic refrigerant for use at low field. Highlights: Pr2Co7 intermetallic compound is prepared by mechanical alloying. It crystallizes in two polymorphic forms hexagonal and rhombohedral structures. The ferromagnetic - paramagnetic was second-order magnetic transition. −ΔSM max of the rhombohedral structure is bigger than the hexagonal one.